Assessment of continuous sky view factor based on ultra-high resolution natural colour images acquired by remotely piloted airborne systems for applications in an urban area of Athens - Nastos, Panagiotis T; Vassilakis, Emmanuel; Nastos, Marina-Panagiota P.; Charalampopoulos, Ioannis; Matzarakis, Andreas (International Journal of Remote Sensing, 2017)
The thermal comfort conditions in a complex urban area is influenced by the surrounding structures and obstacles which modify the incoming radiation fluxes. A measure of this modification is the sky view factor (SVF), which could be estimated in each point of a selected area if a high resolution digital elevation model (DEM), or other urban morphological data including the manmade infrastructure, are available. The goal of this study is to model the continuous SVF for a complex building environment in the campus of National and Kapodistrian University of Athens, based on a high resolution DEM (0.09 m). For this purpose, we applied the structure-from-motion (SfM) technique, which takes advantage of the interpretation of ultra-high resolution colour images acquired by remotely piloted airborne systems, also known as drones or unmanned aerial vehicles. A quantitative analysis, by applying statistical metrics, yields perfect agreement between modelled and observed SVF values, over the examined area. The proposed methodology could be applied for human-biometeorology research in micro scale complex urban environments.